European Union and Development of Romanian Tourism - Gina-Ionela Butnaru; Florina-Iuliana Timu (CES Working Papers, 2011)
At present, both in Romania and in Europe, tourism has the tendency to become one of the biggest industries, with great possibilities of development in the future. This is possible due to the implication of European Union, who has been supporting us not only in the process of economic development, but also in the process of tourism development. This work intends to review what we call tourist phenomenon and the measures applied by the European Union in the development of Romanian tourism.
Keywords: M19; O22; R19; R58; 330; tourism development; Romanian tourism and European Union Romania